Microclimate regulation and energy saving potential from different urban green infrastructures in a subtropical city. (20th July 2019) - Wang, Yafei; Ni, Zhuobiao; Chen, Shaoqing; Xia, Beicheng
Abstract: Urban green infrastructures (GIs) are proved to effectively mitigate urban warming associated with urbanization, and beneficial to the thermal comfort and energy consumption. Quantifying the impacts of urbanization on microclimate and delineating possible urban GIs strategies to maximize their thermal benefits and energy saving potential are thus of importance. This study examined the impacts of the urban growth in Kwai Chung (a fast-developing urban area in Shenzhen, China) on the local microclimate and thermal comfort by conducting the field measurements inside and outside this area. The contribution of urban warming to the daytime mean Ta was up to 4.9 °C in the warm period, which profoundly exacerbated the heat stress. Using a validated ENVI-met model, numerical simulations were conducted to evaluate the thermal benefits and energy saving potentials of the current trees (mainly located in an urban park) and three designed urban GIs (greenway, green roof and grove) in a high-density residential neighborhood. The results revealed that urban park is capable of regulating the hot and cold environment in adjacent urban zones, resulting in improvements of thermal comfort and 3D energy savings of 24.7 and 40.0 kW per day, respectively in the warm and cool periods. Among the designed urban GIs, greenway manifested the best performance on microclimate regulation and energy saving. This research helps the decision-makers and urban planners to delineate the possible urban GIs strategies to optimize the environmental benefit for achieving 'smart' urban growth. Highlights: Thermal impacts of urbanization in a fast-developing city was determined. Thermal benefit and energy saving of 3 designed green infrastructure were evaluated. Urbanization exacerbated urban heat stress with increment of 4.9 °C daytime mean Ta. Urban park potentially saved energy of 24.7 kW in summer and 40.0 kW in winter. Greenway performed best in microclimate regulation and energy saving.